Rancang Bangun Sistem Informasi Layanan Elektronik Program Studi Teknik Informatika Fakultas Teknik Universitas Mataram - Baiq Nia rahmawati; I Wayan Agus Arimbawa; Ahmad Zafrullah Mardiansyah (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2020)
The design of the PSTI Electronic Service Information System, Faculty of Engineering, University of Mataram is an advanced system that supports the correspondence process that is asked by students to ask for permission, such as research permit, submission of supporting data for the final assignment, submission of data for coursework, submission to college transfer , invite leave and be active again. This system works to make outgoing letters needed by students for submitting applications requested for this form above or processed by other parties as to the Admin Study Staff Program. The test results with the black box method all functions are by following the system proposed and expected by system users, especially students and admins. Based on the results of testing the Mean Opinion Score method, it can be concluded that 64% of respondents agreed and 36% of respondents stated that they strongly agreed with the design of electronic service information systems, informatics engineering study programs, engineering faculty, Mataram University.